Autism spectrum mixed neurodevelopmental disorder associated with 6q27 deletion and multiple copies within 20q11.23: a case study. Issue 3 (2014) - ,; ,; ,; ,
Abstract : Purpose – Copy Number Variations (CNVs) are not infrequently observed in aberrant neurodevelopment. CNVs can alter gene expression and have been linked to a wide range of neuropsychiatric disorders. The purpose of this case study is to report the association of CNVs with a mixed neurodevelopmental disorder.Design/methodology/approach – Array‐Comparative Genomic Hybridisation analysis was carried out in a case of an eight‐year‐old boy presenting with a mixed neurodevelopmental disorder including autism spectrum disorder, intellectual disability, tic disorder, anxiety and severe aggression. The child's parents also underwent the same investigation.Findings – A 6q27 deletion and multiple copies within 20q11.23 were identified. The boy's father shared the 6q27 deletion and his mother also had multiple copies within 20q11.23.Originality/value – This is the first report linking the combination of 6p27 and 20q11 CNVs with a mixed neurodevelopmental presentation. Identifying CNVs that may underlie aberrant neurodevelopment is likely to assist in unravelling the aetiology of neurodevelopmental and psychiatric disorders and lead to more effective strategies for their characterisation and management.